Absenteeism as a mechanism of repression of demand in the Brazilian public sector: accounting reflex in federal education public institutions - Mendes, Nara Cristina Ferreira; Serrano, André Luiz Marques; Ferreira, Lucas Oliveira Gomes; Meneses, Pedro Paulo Murce (Open Science Journal, 2021)
Absenteeism is seen as a critical problem in public organizations, since the factors that generate it negatively impact the productivity of organizations. In this sense, considering that Federal Institutions of Higher Education represent almost half of the entire workforce existing in the Federal Executive Branch, this article aims to identify absenteeism, as well as its typification, in addition to measuring its accounting reflex. The methodology adopted was panel data analysis, through the analysis of the absenteeism index with time series from 2008 to 2018. The research findings reinforce that absenteeism is more representative when it is due to a stricto sensu graduate program and medical licenses. Furthermore, it was found that the absenteeism rate doubles every 5 years.